Description of six new species of Oriental Paduniella (Insecta: Trichoptera: Psychomyiidae) - Johanson, Kjell Arne; Oláh, János (Zootaxa, 2010)
Six new species of Paduniella (Insecta, Trichoptera, Psychomyiidae) from Asia are described and illustrated: P. burmana (Burma), P. dongdata (Vietnam), P. monga (Vietnam), P. nama (Vietnam), P. sabarmata (India), and P. taya (Vietnam). The male genitalia of P. sampati Malicky & Chantaramongkol and P. semarangensis Ulmer are re-described and illustrated based on new material from Vietnam.